2021
DOI: 10.3390/geosciences11040177
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of Deformable Blocks: Application to the Opening of the Tyrrhenian Basin and the Formation of the Apennine Chain

Abstract: We describe the opening of back-arc basins and the associated formation of accretionary wedges through the application of techniques of deformable plate kinematics. These methods have proven to be suitable to describe complex tectonic processes, such as those that are observed along the Africa–Europe collision belt. In the central Mediterranean area, these processes result from the passive subduction of the lithosphere belonging to the Alpine Tethys and Ionian Ocean. In particular, we focus on the opening of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…The area of study (Figure 1) is located in the Apennine fold and thrust belt. This area represents the most recent expression of the geodynamic process that produced the Mediterranean basins after the collision between Europe and Africa, which started during the late Cretaceous period and was followed by Oligocene and Neogene periods' slab-retreat events [15,17,[19][20][21][22].…”
Section: Geological Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The area of study (Figure 1) is located in the Apennine fold and thrust belt. This area represents the most recent expression of the geodynamic process that produced the Mediterranean basins after the collision between Europe and Africa, which started during the late Cretaceous period and was followed by Oligocene and Neogene periods' slab-retreat events [15,17,[19][20][21][22].…”
Section: Geological Backgroundmentioning
confidence: 99%
“…The tectonic evolution of the entire area is strongly debated due to the complexity of the geodynamic processes that generated the mountain chain (e.g., [9,21,23,24]). Several authors have proposed models based on stratigraphic and structural analysis of transects oriented along the flow lines of relative motion [25,26], whereas others have followed an approach based on the laws of plate kinematics [22,27]; however, all of these studies found a Moho step in correspondence with the Apennines chain, caused by a discontinuity between the subducting Adriatic plate and the Tyrrhenian back-arc domain to the west. The Moho step (~10 km) was also observed by recent geophysical studies of Italian and European Moho geometry [12,21,[28][29][30][31][32][33].…”
Section: Geological Backgroundmentioning
confidence: 99%